ANALISIS KESELAMATAN LALU LINTAS BERDASARKAN KELENGKAPAN KESELAMATAN BERKENDARA - Sarep, Petrus Yohanes Nabasin; Didoek, Gilbert Markpeter Targanski; Pora, Yuyun Indriani; Keraf, Benedictus Sani; Seran, Engelbertha N. Bria (Eternitas: Jurnal Teknik Sipil, 2023)
Traffic safety refers to efforts to prevent accidents and injuries related to the use of roads and transportation systems. This includes various aspects designed to maintain the safety of drivers, passengers, pedestrians and other road users. The main goal of traffic safety is to reduce the risk of accidents, protect human life, and reduce the impact of injuries caused by traffic accidents. Many factors can cause road accidents, including driver negligence in driving equipment and driving behavior that does not pay attention to safety. This research was conducted to determine driving discipline and safety. The survey was conducted on Jalan Kaniti Dusun 4 Penfui Timur for 4 days starting from 26 July 2023 to 1 August 2023 (Saturdays and Sundays where surveys were not carried out) from 08.00 to 16.00 WITA. The discussion of this article will begin with an overview of traffic safety and equipment for driving and planned activities.